Statistical techniques in business & economics - Lind, Douglas A.; Marchal, William G.; Wathen, Samuel Adam. (New York, NY : McGraw-Hill Education, 2021)
"We have made many changes to examples and exercises throughout the text. The section on "Enhancements" to our text details them. The major change to the text is in -response to user interest in the area of data analytics. Our approach is to provide instructors and students with the opportunity to combine statistical knowledge, computer and statistical software skills, and interpretative and critical thinking skills. A set of new and revised exercises is included at the end of chapters 1 through 18 in a section titled "Data Analytics.""--
Includes index.
ESS
Karim International
Keywords: Economics -- Statistical methods; Commercial statistics